Traditional Performing Arts and Islamization: Ricklefs' Framework Amid Historical Discontinuity in Sleman, Yogyakarta - Muhyidin (Advanced Studies on Socio-Economy Development, 2025)
This research aims to explore the portrayal of Javanese traditional performing arts within Merle Calvin Ricklefs' work on the history of Islamization in Java, recognized as one of the most comprehensive historical accounts on this subject. Ricklefs' trilogy includes